Anti‐MDA‐5 antibody‐positive clinically amyopathic dermatomyositis with rapidly progressive interstitial lung disease treated with therapeutic plasma exchange: A case series. Issue 1 (21st August 2020) - Saito, Tomohiro; Mizobuchi, Masahide; Miwa, Yusuke; Sugiyama, Motonori; Mima, Yuuki; Iida, Ayana; Kanazawa, Nobuhiro; Morikawa, Tomoki; Hayashi, Junichi; Fukuda, Kei; Shikida, Yasuto; Suzuki, Taihei; et al.
Abstract: We present six cases of antimelanoma differentiation‐associated gene 5 antibody (anti‐MDA5‐Ab)‐positive clinically amyopathic dermatomyositis (CADM) with rapidly progressive interstitial lung disease (RP‐ILD), which is known to have a poor prognosis. The outcomes of these cases are described after treatment with therapeutic plasma exchange (TPE). Clinical and therapeutic data for patients with CADM with RP‐ILD were collected retrospectively from medical records. All six patients received early intensive care including high‐dose corticosteroids, intravenous cyclophosphamide, and a calcineurin inhibitor, but lung disease and hypoxia became more severe. TPE was performed over a median of 9.5 sessions (range 3‐14) per patient, and the median duration from admission to TPE was 23 days. Three patients received combined direct hemoperfusion using a polymyxin B‐immobilized fiber column (PMX‐DHP) therapy on successive days to manage acute respiratory failure. Four patients survived and two died due to respiratory failure. In the survival cases, ferritin decreased, and ferritin and KL‐6 were lower at diagnosis. The patients who died had a higher alveolar‐arterial oxygen difference and more severe lung lesions at the time of initiation of TPE. These findings indicate that a combination of conventional therapy and TPE may be useful for improvement of the prognosis of CADM with RP‐ILD at the early stage of onset.